Pengembangan Media Pembelajaran Bahasa Inggris Kelas 10 untuk Meningkatan Writing Skills Siswa - Romi Siswanto (Jurnal Didaktika Pendidikan Dasar, 2022)
Language competence consists of four competences to master it. The four competences are speaking, listening, writing, and reading. Speaking can be done spontaneously, but writing must be planned and organized. The purpose of this study is to design an applicable android operation-based learning media to help pupils develop their English writing proficiency. This study uses the Research and Development approach which was acclimated in the development of the ADDIE model. The experimenter designed a education media called "Learn English Better". This education media has been validated by media experts and material experts before being tried out on pupils. The data collection instruments used were questionnaires and interviews. The results of media validation attained a value of 84,6, for material validation a value of 76,36 was attained, and the results of the implementation of this media attained a value of 73,2. Based on the results over, the experimenter concludes that the Learn English Better android operation is suitable to develop English writing proficiency in SMA Negeri Jombang.